VO2-based thermally tunable emitter and preliminary design of switching for mid-infrared atmospheric windows - Wen-zhuang Ma (Elsevier, 2021)
An atmospheric window is greatly significant in the radiative cooling field. In this study, we preliminarily design a thermally tunable metamaterial emitter that can be used as an internal and external emission switch for a mid-infrared atmospheric window (3.5–5 and 8–14 μm). The proposed emitter has a multilayer metal–dielectric–metal micropyramid structure with thermochromic VO2 spacers. Its broadband emission and thermal tunability are due to the resonance of the hybridization of separate magnetic polaritons, surface plasmon polaritons, and the thermal phase-transition characteristics of VO2. The structure has a warming effect at the temperature below the phase-change temperature. On the contrary, it has a cooling effect at the temperature above the phase-change temperature. These phenomena show the emitter’s potential application in smart temperature control systems.